Implementation of Student Discipline in Improving Learning Achievement at MA Fatahillah Lohbener Indramayu - Chaniago Ramdhan (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2022)
The purpose of this study was to find out how the implementation of student discipline in improving learning achievement in class XI MA Fatahillah Lohbener Indramayu. This type of research is field research using a qualitative approach and using descriptive analysis, with data collection techniques carried out by observation, documentation, interviews, and questionnaires. The conclusion of the study is that the implementation of student discipline at MA Fatahillah Lohbener Indramayu is going well and students obey the rules made by the school. Then the effort to implement student discipline in improving learning achievement is to apply time discipline, dress discipline, worship discipline, study discipline, school activity discipline and apply strict punishments. From these efforts it is evident that there has been an increase in student discipline. The improvement is that students can implement discipline at school, the enthusiasm for learning and student learning outcomes are increasing, as evidenced by the many academic achievements obtained by MA Fatahillah Lohbener Indramayu students. Keywords: Discipline, learning achievement, students